2022
DOI: 10.3390/ijerph19116902
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Duration and Physical Fitness in Children Aged 3–6 Years: A Cross-Sectional Study from China

Abstract: Aim: To explore associations between sleep duration and physical fitness (PF) of children aged 3–6 years. Methods: This study investigated the sleep duration and PF data of children aged 3–6 years by stratified random sampling. The restricted cubic spline model and binary logistic regression analysis were mainly used for the empirical analysis of the correlation effect between sleep duration and PF. The final data had a total of 21,857 children, of which 11,245 (51.45%) were boys and 10,612 (48.55%) were girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The risk of low PF in children with sleep abnormalities is 1.1 times higher than in children with normal sleep. 34 Barrios et alfound that preschool children with persistent sleep deprivation showed more attention deficits, hyperactivity disorder, and lower levels of PF compared to normal children. 35 However, the mechanisms of the association between sleep and PF in children are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of low PF in children with sleep abnormalities is 1.1 times higher than in children with normal sleep. 34 Barrios et alfound that preschool children with persistent sleep deprivation showed more attention deficits, hyperactivity disorder, and lower levels of PF compared to normal children. 35 However, the mechanisms of the association between sleep and PF in children are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, MVPA is not advocated as a replacement for sleep due to the important role of sleep in the health and development of preschool children. 41 However, Xiong et al, 2022; found an inverted U-shaped relationship between sleep duration and PF levels in preschoolers, 34 with both insufficient and excessive sleep time increasing the detection of low PF levels. In addition, this study showed that 5 min was the turning point for dose-response change in MVPA replacement, suggesting that an increase in MVPA of 5 min per day may have the most efficient impact on muscular strength and speed-agility improvement.…”
Section: Discussionmentioning
confidence: 99%